Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata) - Bedjanič, M.; Conniff, K.; Dow, R.a.; Stokvis, F.r.; Verovnik, R.; Tol, J. Van (Zootaxa, 2016)
The 22 Sri Lankan representatives of the family Platystictidae, all endemic to the island and belonging to the distinct endemic subfamily Platystictinae, are revised, and a new reconstruction of the phylogeny based on molecular characters is provided. Five new species are described: Ceylonosticta venusta sp. nov. (holotype ♂: Rambodde Falls, at the tunnel; Nuwara Eliya District, Central Province; N7.0489, E80.6961; 12-vii-2012; to be deposited at National Museum of Natural History, Colombo, Sri Lanka), C. inferioreducta sp. nov. (holotype ♂: Norton Bridge, stream on the B43 road 1.5km WNW of Norton Bridge; Nuwara Eliya District, Central Province; N6.9171, E80.5075; 28-vii-2009; to be deposited at National Museum of Natural History, Colombo, Sri Lanka), C. mirifica sp. nov. (holotype ♂: Uwella, primary forest on the road Uwella-Ratnapura, 11.5km NW of Balangoda; Ratnapura District, Sabaragamuwa Province; N6.6968, E80.6059; 16-vii-2012; to be deposited at National Museum of Natural History, Colombo, Sri Lanka), Platysticta secreta sp. nov. (holotype ♂: Hasalaka; Kandy District, Central Province; N7.3535, E80.9509; 31-v-1975; deposited at National Museum of Natural History, Smithsonian Institution, Washington, USA) and P. serendibica sp. nov. (holotype ♂: Kanneliya; Galle District, Southern Province; N6.2291, E80.3834; 8 & 9-vi-1975; deposited at National Museum of Natural History, Smithsonian Institution, Washington, USA). Additionally, a determination key, figures showing morphological details and coloration in life, as well as distribution maps for all species are presented. Based on molecular analysis of 21 taxa, the phylogeny of Platystictinae is presented and discussed from the zoogeographical and paleogeographical point of view. Sri Lankan species, traditionally placed in the genera Platysticta Selys and Drepanosticta Laidlaw / Ceylonosticta Fraser, separated into distinct clades within the subfamily as presently defined, but the monophyletic nature of the Platystictinae and its Sri Lankan endemicity is confirmed. For the South Indian species, formerly known as Platysticta deccanensis, morphological and molecular analyses demonstrated that it does not belong to the Sri Lankan clade and a new genus Indosticta gen. nov. is erected to accommodate it.